Never Ask for a Lighter Rain but a Stronger Umbrella - Pande, Saket; Haeffner, Melissa; Blöschl, Günter; Alam, Mohammad Faiz; Castro, Cyndi; Di Baldassarre, Giuliano; Frick-Trzebitzky, Fanny; Hogeboom, Rick; Kreibich, Heidi; Mukherjee, Jenia; Mukherji, Aditi; Nardi, Fernando; et al. (Frontiers in Water, 2022)
In a recent editorial in the journal Nature Sustainability, the editors raised the concern that journal submissions on water studies appear too similar. The gist of the editorial: “too many publications and not enough ideas.” In this response, we contest this notion, and point to the numerous new ideas that result from taking a broader view of the water science field. Drawing inspiration from a recently hosted conference geared at transcending traditional disciplinary silos and forging new paradigms for water research, we are, in fact, enthusiastic and optimistic about the ways scientists are investigating political, economic, historical, and cultural intersections toward more just and sustainable human-water relations and ways of knowing.